Molluscan Records from West Texas - E. P. Cheatum; Richard Fullington; Lloyd Pratt (Hello World!, 1972)
This report is based upon molluscan species collected in West Texas by the writers during the past eight years. Four of the collecting trips were made within the past three years and were sponsored by the Dallas Natural Science Association. Eighteen other collecting trips were sponsored by the Fort Worth Museum of Science and History. Therefore, this is a joint listing of collections. Lloyd Pratt who has worked independently from the other writers has done intensive collecting of mollusks in the Trans-Pecos, particularly in the Chisos Mountain range.